Analisis terhadap Penerapan Manajemen Risiko Kredit dalam Meminimalisir Kredit Bermasalah pada Bank Jatim (Studi pada PT. Bank Jatim TBK Kantor Pusat Surabaya) - Natasya, Aginsha Caurel; Rachmawati, Titiek (Universitas Muhammadiyah Surabaya, 2025)
In every credit provision, credit risk is inseparable. Credit risk is the risk of loss that can be associated with the possibility of the debtor's failure to pay his obligations. This risk arises due to poor performance from the debtor's inability to fulfill all or part of the agreements that have been agreed upon with the bank. The risk in providing credit can be called non-performing loans (Non-Performing Loans). In this regard, the author intends to analyze the bad debts that have occurred in banking in East Java. Currently, East Java banking also continues to play an active role in providing credit by targeting a reduction in the number of bad loans (Non-Performing Loans) of 5%. The Corporate Secretary of Bank Jatim targets a reduction in the risk of bad loans (NPL) for 2024 to below 3%. This strategy was taken to improve credit quality and maintain the health of the bank's loan portfolio in line with the growth in credit distribution which is also targeted to increase by 22.04% to Rp. 66.83 trillion. The data collection technique used is Library Research, which is research by reading books, literature, written reports and scientific papers that are related to the problems discussed. And Field Research, which is data collection by direct observation of the objects studied by means of observation and interviews. The results of this study can be concluded that Risk Management at PT. Bank JATIM Head Office has been implemented well. However, in its implementation there are still shortcomings, namely Credit analysis is not careful enough so that it provides credit to debtors who currently have consumer loan facilities from other banks, monitoring of debtors and reporting of visit results in call reports has not been carried out in accordance with applicable provisions.